Conjoint analysis of transcriptome and metabolome profiles of normal captivity and arch soil free-range in Meishan pigs - Ying Liu; Yanlong Su; Zhijie Zhou; Jie Zhu; Qianqian Zhu; Peng Xie; Shiquan Qian; Liwei Wang; Tong Qin; Gang Zhou (Frontiers in Veterinary Science, 2023)
The hygiene hypothesis has been advanced as a potential explanation for the increasingly high levels of atopy and allergic disease in the general human population. In an effort to conduct a more detailed study of the link between immune activity and the hygiene hypothesis, Meishan pigs raised under normal captivity (NC) or arch soil free-range (ASF) conditions were selected as an experimental model system. Cytokine levels were found to differ significantly between these two groups consistent with a difference in cellular immune status. Integrated transcriptomic and metabolomic profiling of duodenal tissue samples from Meishan pigs were then performed, leading to the identification of differentially expressed genes (DEGs), differentially abundant metabolites (DAMs), and key pathways that were able to distinguish the NC and ASF groups. This approach led to the identification of 1,113 DEGs, as well as 577 and 372 DAMs in positive and negative ion modes, respectively. When an interaction network incorporating DEGs and metabolites associated with immune responsivity was constructed, it included factors such as 9-cis-Retinoic acid, (9Z,11E)-(13S)-13-Hydroxyoctadeca-9,11-dienoic acid and (10E,12Z)-(9S)-9-Hydroxyoctadeca-10,12-dienoic acid. Functional enrichment analyses confirmed that identified DEGs and DAMs were associated with immune-related pathways including the intestinal IgA production and PPAR signaling pathways. Together, these results offer new insight into the roles that particular genes and metabolites enriched in response to environmental stressors in free-range Meishan pigs may play in the regulation of cellular immunity, thus offering a foundation for future efforts to better understand the immunological mechanisms underlying the hygiene hypothesis.